Drawing on students’ lived experiences in emergency remote teaching (ERT): reflections from a critical pedagogy inspired writing class - Joseph Jeyaraj, Joanna (Routledge, 2021)
This study focuses on one particular attribute of critical pedagogy, which is engaging with the lived experiences of students. The aim was to examine how students experienced writing about their immediate realities under emergency remote teaching and learning conditions. Students were asked to write about what they had learnt as a result of being impacted by the Covid-19 pandemic. Then, they were invited to post these stories on an online platform. Four themes emerged from students’ reflections on writing about this experience. First, they felt that writing was purposeful and that they were writing for a larger audience. Second, because time and space for critical reflection was provided, some level of renewed dispositions towards the self and others was experienced. Third, writing became an emotionally charged process. Finally, numerous students reflected that writing about something so personal and being encouraged to share their experiences on a public online platform brought about a sense of discomfort. Hence, teachers who want to engage with critical pedagogy under “emergency” conditions may need to recontextualise their practice to suit the present needs and realities of students.